Purulent meningitis caused by Rhodococcus equi: A case report. Issue 24 (June 2018) - Cui, Le-xiang; Gu, Li-na; Hou, Yan-bo; Zhang, Bei-lin; Liu, Jing-yao
Abstract: Rationale: Purulent meningitis refers infection of the subarachnoid space by various purulent bacteria and the corresponding inflammation of the leptomeninges. However, purulent meningitis due to Rhodococcus equi is extremely rare. Patient concerns: A 40-year-old man presented with fever and intermittent headache for 6 days. Two hours prior to admission, he developed epileptic seizures. Diagnoses: Brain computed tomography and magnetic resonance imaging showed intracerebral malacic lesions. Bacterial culture of cerebrospinal fluid revealed the presence of R. equi . A diagnosis of purulent meningitis caused by R. equi was made. Interventions: The patient was treated with intravenous meropenem (1000 mg every 8 hours) for 19 days; then he was discharged and instructed to continue the intravenous meropenem for two weeks. After a follow-up period of 2 months, the patient had recovered completely. Outcomes: After a follow-up period of 2 months, the patient had recovered completely. Lessons: Central nervous system infection caused by R. equi is rare. Early bacterial culture of CSF is important for timely diagnosis. With sufficient antibiotic therapy, the prognosis can be favorable.